Micafungin antifungal prophylaxis in children undergoing HSCT: can we give higher doses, less frequently? A pharmacokinetic study. (21st February 2018) - Chandra, Sharat; Fukuda, Tsuyoshi; Mizuno, Kana; Davies, Stella M; Teusink-Cross, Ashley; Tarin, Rich; Marsh, Rebecca A; Vinks, Alexander A; Mehta, Parinda A
Abstract: Background: Micafungin has a distinct advantage for antifungal prophylaxis in HSCT owing to its better safety profile, specifically in terms of hepatic and renal toxicity. In children, prophylactic micafungin is given as either 1 mg/kg every day or 3 mg/kg every other day. Objectives: We performed a prospective single-centre observational study that investigated the pharmacokinetics (PK) of a single 5 mg/kg dose of micafungin in young children undergoing HSCT, to ascertain the eventual feasibility of twice-weekly prophylactic administration. Methods: Nine children, ≤10 years of age undergoing HSCT, were enrolled and received a single intravenous dose of 5 mg/kg micafungin. Blood samples were obtained for PK analysis. Micafungin plasma concentration of >0.2 mg/L was chosen for target attainment (i.e. considered adequate prophylactic concentration). In addition, a population PK model was developed based on current and our previous PK study data. We also evaluated PK model-based simulation of PK profiles and target attainment using Monte Carlo simulation, for several dosing scenarios. Results: Mean clearance was 15.3 mL/h/kg (range 11.0–21.4 mL/h/kg) and the mean elimination half-life was 11.6 h (range 7.8–16.6 h). The mean concentration at 96 h was 0.11 mg/L (range 0.03–0.26 mg/L). Eleven percent ( n  =   1) of patients achieved target attainment at the end of 96 h. Simulation data showed that 1 mg/kg daily dosing and 3 mg/kg alternate-day dosing strategies achieved at least 99% and 81% target attainment, respectively, whereas a 5 mg/kg with 3 day-interval dosing strategy resulted in 64%, 72% and 84% target attainments in patients with body weights of 10, 20 and 30 kg, respectively. Conclusions: Micafungin at 5 mg/kg dosing did not achieve target attainment at the end of 96 h for antifungal prophylaxis in children undergoing HSCT. Simulation data suggest that a dosing strategy of micafungin at 5 mg/kg every 72 h is more likely to achieve target attainment in children with a higher body weight in comparison with children with a lower body weight. A cautious approach is advisable when using a high, but less frequent, dosing strategy in very young children.